Aplikasi Komunikasi Islam dalam Kegiatan Pembelajaran di Perguruan Tinggi - Mustafa, Ali (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2024)
This article explores the application of Islamic communication in higher education learning, focusing on three main aspects: communicator, message, and media. Through a literature review with a qualitative approach, it was found that lecturers, as communicators, are not only in charge of teaching, but also act as role models in applying Islamic principles when interacting with students. The material or message conveyed in learning must adopt Islamic teachings and values, in order to form good morals in students. Learning media must also be carefully selected to ensure that the content presented supports the delivery of Islamic messages and is in line with Islamic teachings. Overall, the application of Islamic communication in higher education learning can not only improve the effectiveness of the learning process, but also contribute to the achievement of comprehensive Islamic education goals. In conclusion, the integration of Islamic communication is essential in shaping graduates who excel academically and have high moral and spiritual integrity.